Effects of Aerodynamic Characteristic at Different Velocity for Three Different Helmets and Neck Design Using Computational Fluid Dynamic Analysis - Mat Nazeri, Muhammad Arif; Yasak, Fuad; Ishak, Izuan Amin (Journal of Emerging Technologies and Industrial Applications, 2023)
Helmet is one of the mechanism or safety element in motorcycle that protect motorcyclist from major injury in head and neck. Protective helmet may reduce the risk of death and head injury in motorcycle collision. However, there is still remain a large gap in knowledge regarding the effectiveness of different types of helmets in preventing injuries especially the one that relate to neck muscle strain occurs during riding. Most of the motorcyclist usually express their feeling of dissatisfaction with the fits of their helmets and it affected the posture of motorcyclist during riding. Bad posture of human caused different type of muscle strain on body. This study was focusing in research regardless neck strain during prolonged riding of motorcycle on a road. The main problem happened for air flow is how different type of helmet can cause the neck pain in motorcyclist since the different of velocity of air flow passing through may affect the muscle fatigue located on neck. In this research, the flow of air had simulated by using Computational Fluid Dynamics (CFD) software which is ANSYS-FLUENT to visualize the external flow streamline, which passed through the helmet model. It passed through three different helmets with three different velocities from 20m/s, 25m/s and 30m/s. The pressure distribution and velocity flow of helmet model are analyzed by representing it on streamlines and contour. As for the result, when the velocity is increase until 30m/s, it will create a low pressure at 266 Pa and very high velocity around the helmet. Thus, the turbulence rate in the region is very high. The result obtained shows the minimum average maximum principle elastic strain of neck occurs to the full-face helmet at 3.44×10-09. Full-face helmet meet the safest criteria compared to the other design in term of neck pain.